2012
DOI: 10.1111/j.1523-5378.2011.00923.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of Inflammation and Cytotoxin‐Associated Gene A Positive Strains of Helicobacter Pylori in Cardiac Syndrome X

Abstract: The CagA+ strain of H. pylori, can not only be a trigger, and may also have a role via chronic inflammation in the pathogenesis of CSX.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…CagA-positive H. pylori infection plays a critical role in various diseases via changes in inflammation and immune response. The data from one study[19] demonstrated that a CagA+ strain of H. pylori not only can be a trigger but also may result in chronic inflammation involved in the pathogenesis of cardiac syndrome X (CSX). In addition, the cag pathogenicity island (cagPAI) is critical for H. pylori pathogenesis in bile duct cells[20].…”
Section: Discussionmentioning
confidence: 99%
“…CagA-positive H. pylori infection plays a critical role in various diseases via changes in inflammation and immune response. The data from one study[19] demonstrated that a CagA+ strain of H. pylori not only can be a trigger but also may result in chronic inflammation involved in the pathogenesis of cardiac syndrome X (CSX). In addition, the cag pathogenicity island (cagPAI) is critical for H. pylori pathogenesis in bile duct cells[20].…”
Section: Discussionmentioning
confidence: 99%
“…Although we have evaluated systemic inflammation through this analyte, we agree that other parameters should be useful and more specific to determine a possible link between H. pylori's infection and systemic inflammation. In example, some studies have considered to study as inflammation markers interleukin-6 (IL-6), IL-8 and TNF-α, which seems to be specially related to bacterial infection (3,34) . As mentioned above, regarding the remarkable association between the presence of anti-CagA antibodies and higher tissue damage, although with no systemic responses through the measurement of hsCRP levels, we encourage the development of further studies involving additional inflammatory markers that could be related to higher systemic inflammation in functional dyspeptic people carrying H. pylori and its virulence factor.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, many studies have been demonstrated an association between H.pylori infections and some vascular diseases, such as ischemic heart disease [16]. Chronic infection may be accompanied by persistently increased production of inflammatory metabolites [8]. H.pylori produces some antigenic substances, including heat shock protein, urease, and lipopolysaccharide, all of which can be taken up and processed by lamina properia macrophages and active T-cells and cause increased production of inflammatory cytokines such as interleukine-1 (IL-1), IL-6, tumor necrosis factor alpha (TNFa), and most important IL-8.…”
Section: Discussionmentioning
confidence: 99%
“…Hcy is a sulphur amino acid formed from methionine during transmethylation, and is either salvaged to methionine by a folate and co-balamin-dependent re-methylation reaction or directed toward degradation by vitamin B 6 -dependent enzyme cystathionine beta-synthase [6,7]. Also, previous studies has shown an association between viral and bacterial infections including Helicobacter pylori (H.pylori) and some vascular disease such as CSX [8]. H.pylori is a spiral shaped positive gram that cause the most common chronic bacterial infection in the world [9].…”
Section: Introductionmentioning
confidence: 99%